PELATIHAN COMPRESSION ONLY-CPR EFEKTIF MENINGKATKAN KETEPATAN KOMPRESI DADA PADA ORANG AWAM - Nofiyanto, Muhamat; Darussalam, Miftafu; Adi Setiawan, Arif (MEDIA ILMU KESEHATAN, 2019)
Background: Many studies show a low rate of immediate chest compression in OHCA cases. One of the factors that inhibits is the lack of knowledge of lay people who witness cases of cardiac arrest. Objective: To determine the effect of providing compression-only CPR training on chest compression skills in lay people Methods: This research used pre-experiment with one group pre-post test design, with a total of 28 respondents, using simple random sampling technique. Respondents measured chest compression skills before training, then provided training for 120 minutes.Wilcoxon test was used to analyze data sets. Results: There were almost the same number between male and female respondents, and most have never received CPR training. Only 5 respondents had received previous training, with details of 3 years, 6 years, 8 years, 9 years and 11 years ago. There was a difference in the accumulation of the accuracy of chest compression before and after training with a p-value of 0,000. Conclusion: Compression only-CPR training can improve chest compression skills, especially aspects of accuracy of compression. Broader training and intensification of training programs are needed to realize emergency preparedness in the campus community. Keywords: Cardiac arrest, CPR, training